DIGITALISASI KOPERASI SYARIAH MODERN DALAM UPAYA MENINGKATKAN KUALITAS KELEMBAGAAN KOPERASI SYARIAH DI DKI JAKARTA (An Nawawi, 2025)
Cooperatives in Indonesia play an important role as an economic pillar of society. Still, many operate conventionally and face various challenges such as poor management, low interest from the younger generation, transparency and accountability issues. This study proposes the transformation of Islamic cooperatives into modern cooperatives through digitalisation to improve efficiency, effectiveness and services to members.  Digitalisation is expected to speed up business processes, improve market access and provide more innovative services. By using information and communication technology, Islamic cooperatives can strengthen their institutions and better meet the needs of their members.  In this context, this study uses a descriptive qualitative method to describe the phenomenon of digitalisation of Islamic cooperatives in Jakarta.  The findings show that digitalisation can improve cooperatives' transparency, accountability, competitiveness, contribute to more inclusive and sustainable economic growth.  The research highlights the importance of support from the government and other stakeholders to develop modern cooperatives in Indonesia, focusing on Islamic cooperatives as agents of economic change.
Keywords: Digitalization, Transformation, Sharia Cooperatives, Transparency, Accountability